Avaliação das concentrações de pesticidas organoclorados em águas superficiais pela otimização da técnica USAEME - Nakamura, Estéfano (2015)
The main goal of this study was to determine organochlorine pesticides (OCP) concentrations from Taquara River using optimized USAEME extraction technique ((Ultrasound - Assisted Emulsification Microextraction) and analysis by GC-MS (Gas Chromatography-MassSpectrometry). The extraction process was optimized on the determination of 16 organochlorine pesticides simultaneously (α-BHC, γ-BHC, β-HC, δ-BHC, heptacloro, aldrin, heptacloro epóxido, γ-clordano, endosulfan I, α-clordano, 4,4’-DDE, dieldrin, endrin, endosulfan II, 4,4’-DDD, endrin aldeído, endosulfan sulfato, 4,4’-DDT, endrin cetona e metoxicloro). Therefore, the influence a DCCR design (Delineation Central Composite Rotational) with 20 experiments was proposed, in which the following factors were evaluated: extractor solvent volume (chloroform), manual agitation time and time of ultrasound exposure. Among the factors, solvent volume was the most significant parameter to all 20 pesticides, mainly for the fact that its volume influenced directly the extract dilution factor, with the optimum value 122 µL. For manual agitation, time superior to 1 second were not significant to enhance extraction. For ultrasound assisted phase, time superior to 14 minutes negatively influenced the extraction due to elevation on system temperature. Higher temperatures promote higher solubilization of chloroform in the aqueous phase, diminishing extraction efficiency. Percentage of recovery of the compounds in real samples fortified in three different levels (0.5, 1.0 and 2.0 µg L 1) varied from 65,35 to 127,14%, which can be considered adequate for environmental analysis. Limit of Detection (LOD) and Limit of Quantification (LOQ) varied from 0.13 to 0.50 and 0.39 to 1.52 µg L-1, respectively. As for the presence of the OCP in real samples, it was detected the endosulfan family in 78% of the samples. DDT and its metabolites, DDD and metoxiclor, were found, exclusively on site 3, and for May, June and November samples only. Those facts reinforce that even after decades of the prohibition of use of these pesticides, mostly for DDT, they are still found in the environment.